MALE HYPOGONADISM AT A TERTIARY CARE HOSPITAL IN KARACHI, PAKISTAN - Ram, Nanik; Asghar, Ali; Hashmi, Fauzan; Islam, Najmul (Journal of Ayub Medical College Abbottabad, 2012)
Background: Male hypogonadism is defined as '˜inadequate gonadal function, manifested by deficiency in gametogenesis and/or secretion of gonadal hormones'. Signs and symptoms of hypogonadism depend primarily on the age of onset. It can be classified according to the site primarily involved: the gonads, the hypothalamus, or the pituitary gland. The objective this study was to determine the presentation and aetiology of male hypogonadism seen in a tertiary care hospital. Methods: This cross-sectional study was conducted at Endocrine Clinics, Aga Khan University Hospital Karachi. Data of male patients with hypogonadism who attended clinics during January 2009 to August 2011 were reviewed. All male patients with clinical and biochemical evidence of hypogonadism were included in the study. Patients with Diabetes Mellitus, Metabolic Syndrome, Andropause, AIDS, Chronic Renal Failure, and Cirrhosis were excluded. Mean±SD were computed for quantitative variables. Frequency and percentages were computed for qualitative variables. Aetiology of male hypogonadism was categorised as primary and secondary hypogonadism. Results: A total of 85 patients with male hypogonadism attended the endocrine clinic. Mean age of patients was 25±10 years. Clinical presentations were small genitalia (65%), absent secondary sexual characteristics (53%), not attained puberty (47%), infertility (53%), erectile dysfunction (41%) and loss of libido (29%). Seventy-three (86%) patients had hypogonadotrophic hypogonadism (secondary hypogonadism) and 12 (14%) patients had hypergonadotrophic hypogonadism (primary hypogonadism). Among the patients with hypogonadotrophic hypogonadism 38 had idiopathic hypogonadotrophic hypogonadsim, 7 had pituitary adenoma, 6 had empty sella syndrome, 3 had Kallman's syndrome, and 1 patient had haemosiderosis due to thalassaemia major; 18 patients did not undergo brain imaging. Conclusion: Small genitalia, absent secondary sexual characteristics and infertility were the main presenting features of hypogonad men. Majority of patients had hypogonadotrophic hypogonadsim. Keywords: Male Hypogonadism, Erectile dysfunction, Libido, Infertility